System collapse (Murderbot diaries, 07,, 2023)
Am I making it worse? I think I'm making it worse. Following the events in Network Effect, the Barish-Estranza corporation has sent rescue ships to a newly-colonized planet in peril, as well as additional SecUnits. But if there's an ethical corporation out there, Murderbot has yet to find it, and if Barish-Estranza can't have the planet, they're sure as hell not leaving without something. If that something just happens to be an entire colony of humans, well, a free workforce is a decent runner-up prize. But there's something wrong with Murderbot; it isn't running within normal operational parameters. ART's crew and the humans from Preservation are doing everything they can to protect the colonists, but with Barish-Estranza's SecUnit-heavy persuasion teams, they're going to have to hope Murderbot figures out what's wrong with itself, and fast! Yeah, this plan is... not going to work. The Murderbot Diaries All Systems Red Artificial Condition Rogue Protocol Exit Strategy Network Effect Fugitive Telemetry System Collapse.

Light bringer (Red rising saga, 6,, 2023)
The legendary Reaper, Darrow, to defend Mars from a bloodthirsty would-be conqueror, begins his long voyage home, an interplanetary adventure where old friends will reunite, new alliances will be forged, and rivals will clash on the battlefield.